Polysemy of Linguistic Terms in Modern English - Dalieva Madina Khabibullaevna (Researchparks Publishing, 2022)
The article describes issues based on the usage and peculiarities of polysemy of linguistic terms in Modern English. Polysemy is a linguistic universal in the system of European languages. It is based on the asymmetry of the linguistic sign and reflects the principle of saving formal means while conveying the maximum semantic volume. Such polysemy of words in the general literary language is a factor indicating the richness of language visual means. Lexical polysemy gives speech flexibility and allows us to express the delicate shades of thought. This circumstance presents a certain difficulty for the exact understanding of the text and complicates the work of the translator. So, polysemy and synonymy contradict the nature of the functioning and purpose of the term.